a^2+b^2=6 a^3+b^3=4 a+b=

来源:学生作业帮助网 编辑:作业帮 时间:2017/02/24 18:25:25
(a-b)^6*[-4(b-a)^3]*(b-a)^2÷(a-b)=求过程

(a-b)^6*[-4(b-a)^3]*(b-a)^2÷(a-b)=求过程(a-b)^6*[-4(b-a)^3]*(b-a)^2÷(a-b)=求过程 (a-b)^6*[-4(b-a)^3]*

(a^2+1)(-4a^2+1)+a^4-1 3a(a-b)(a+b)-6(b-a)^2a^2-9(a-b)^2= 3a(a-b)(a+b)-6(b-a)^2=

(a^2+1)(-4a^2+1)+a^4-13a(a-b)(a+b)-6(b-a)^2a^2-9(a-b)^2=3a(a-b)(a+b)-6(b-a)^2=(a^2+1)(-4a^2+1)+a^4-1

若a-b=4,3a+2b=6,3a(a-b)+2b(a-b)=( ).

若a-b=4,3a+2b=6,3a(a-b)+2b(a-b)=().若a-b=4,3a+2b=6,3a(a-b)+2b(a-b)=().若a-b=4,3a+2b=6,3a(a-b)+2b(a-b)=(

化简a/b(a-b)-b/a(a-b)其中a=3 b=-2

化简a/b(a-b)-b/a(a-b)其中a=3b=-2化简a/b(a-b)-b/a(a-b)其中a=3b=-2化简a/b(a-b)-b/a(a-b)其中a=3b=-2a/b(a-b)-b/a(a-b

3a^2b-{2a^2b+[9a^b-(6a^2b+4a^2)]-(3a^2b-8a^2)}=

3a^2b-{2a^2b+[9a^b-(6a^2b+4a^2)]-(3a^2b-8a^2)}=3a^2b-{2a^2b+[9a^b-(6a^2b+4a^2)]-(3a^2b-8a^2)}=3a^2b-

a+2b/2a-3b=3 求解4b+2a/9b-6a-4a-6b/3a+6b=?

a+2b/2a-3b=3求解4b+2a/9b-6a-4a-6b/3a+6b=?a+2b/2a-3b=3求解4b+2a/9b-6a-4a-6b/3a+6b=?a+2b/2a-3b=3求解4b+2a/9b

a+2b/2a-3b=3 求解4b+2a/9b-6a-4a-6b/3a+6b=?

a+2b/2a-3b=3求解4b+2a/9b-6a-4a-6b/3a+6b=?a+2b/2a-3b=3求解4b+2a/9b-6a-4a-6b/3a+6b=?a+2b/2a-3b=3求解4b+2a/9b

(3/4)(a+b)(a-b)=2(a-b),题目条件是a,b不等,

(3/4)(a+b)(a-b)=2(a-b),题目条件是a,b不等,(3/4)(a+b)(a-b)=2(a-b),题目条件是a,b不等,(3/4)(a+b)(a-b)=2(a-b),题目条件是a,b不

(a-b)^2*(b-a)^5+(b-a)^3*(a-b)^4=?

(a-b)^2*(b-a)^5+(b-a)^3*(a-b)^4=?(a-b)^2*(b-a)^5+(b-a)^3*(a-b)^4=?(a-b)^2*(b-a)^5+(b-a)^3*(a-b)^4=?原

当a+2b/2a-3b=3,求代数式4b+2a/9b-6a-4a-6b/3a+6b

当a+2b/2a-3b=3,求代数式4b+2a/9b-6a-4a-6b/3a+6b当a+2b/2a-3b=3,求代数式4b+2a/9b-6a-4a-6b/3a+6b当a+2b/2a-3b=3,求代数式

(a-2b)/(a+2b)=3,求(a+2b)/(a-2b)+(3a-6b)/(4a+8b)的解,

(a-2b)/(a+2b)=3,求(a+2b)/(a-2b)+(3a-6b)/(4a+8b)的解,(a-2b)/(a+2b)=3,求(a+2b)/(a-2b)+(3a-6b)/(4a+8b)的解,(a

(3a+2b)*(2a+b)*(a+b)=

(3a+2b)*(2a+b)*(a+b)=(3a+2b)*(2a+b)*(a+b)=(3a+2b)*(2a+b)*(a+b)=(3a+2b)*(2a+b)*(a+b)=6a³+13a

(a-2b)(3a+4b)+(2a-4b)(2a-3b)=(a-2b)*(

(a-2b)(3a+4b)+(2a-4b)(2a-3b)=(a-2b)*((a-2b)(3a+4b)+(2a-4b)(2a-3b)=(a-2b)*((a-2b)(3a+4b)+(2a-4b)(2a-3

已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?

已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?已知a-b/a+b=-3,则代数式2(a

已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?

已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?已知a-b/a+b=-3,则代数式2(a

a-ba+b=12时,求代数式a+b3(a-b) - a-b2(a+b)

a-b\a+b=1\2时,求代数式a+b\3(a-b)-a-b\2(a+b)a-b\a+b=1\2时,求代数式a+b\3(a-b)-a-b\2(a+b)a-b\a+b=1\2时,求代数式a+b\3(a

已知a+b/a-b=7,求2*(a+b)/a-b-a-b/3*(a+b)的值

已知a+b/a-b=7,求2*(a+b)/a-b-a-b/3*(a+b)的值已知a+b/a-b=7,求2*(a+b)/a-b-a-b/3*(a+b)的值已知a+b/a-b=7,求2*(a+b)/a-b

已知a-b/a+b=-3,求a-b/2(a+b)-a+b/a-b的值

已知a-b/a+b=-3,求a-b/2(a+b)-a+b/a-b的值已知a-b/a+b=-3,求a-b/2(a+b)-a+b/a-b的值已知a-b/a+b=-3,求a-b/2(a+b)-a+b/a-b

3(a-b)的平方-7(a-b)+8(a-b)的平方+6(a-b) a-b=2

3(a-b)的平方-7(a-b)+8(a-b)的平方+6(a-b)a-b=23(a-b)的平方-7(a-b)+8(a-b)的平方+6(a-b)a-b=23(a-b)的平方-7(a-b)+8(a-b)的

a^3-ab^2 =a (a^2 -b^2) =a(a+b)(a-b)

a^3-ab^2=a(a^2-b^2)=a(a+b)(a-b)a^3-ab^2=a(a^2-b^2)=a(a+b)(a-b)a^3-ab^2=a(a^2-b^2)=a(a+b)(a-b)你给出的分解因